Pengaruh Komunikasi Interpersonal dan Kualitas Jasa terhadap Kepuasan Pelanggan Pelayanan Aplikasi Visa Australia Di PT Andalan Usaha Cemerlang Jakarta Timur - Suriandhi, Denny (Journal of Economics & Business UBS, 2019)
PT Andalan Usaha Cemerlang is the organization who consider about customer satisfaction. And give quality of interpersonal communication and quality of service. Both of variable have a significant and simultaneous to customers satisfaction with associative quantitative method discovered that both of variable have a coefficient determinant R2 = 0.827 or 82,8% and the rest of amount is 17.2% because of the other factors.Â  Suggestion to PT Andalan Usaha Cemerlang is all quality service and interpersonal communication must be maintained and improved to keep customersâ€™loyality.